AGRESIVITAS ANAK KORBAN EKSPLOITASI DI KAWASAN RAMAYANA PUSAT - Siska Ulandari; Tri Umari; Rosmawati Rosmawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This study aims to describe the forms of aggressiveness committed by child victims of exploitation, aggressiveness experienced by children victims of exploitation and factors that encourage child victims of exploitation to behave aggressively. The subjects in this study were children victims of exploitation aged 6 to 18 years, but had worked on the streets located in the central ramayana area. The research was conducted with a qualitative approach and descriptive type of research and the data obtained in the study came from the results of interviews and observations. The results of the study show that there are still many child victims of exploitation who behave aggressively towards others and there are also many child victims of exploitation who get aggressive treatment from others. Besides that, there are things that become factors for child victims of exploitation to behave aggressively.Key Words: Aggressiveness, Child of Exploitation